Numerical solution on mixed convection heat transfer of ferrofluid over a horizontal circular cylinder - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Mohd Zuki, Salleh (2021)
Becomes highly magnetized in the presence of a magnetic field. Classified into two groups which are surfacted ferrofluid (SFF) and ionic ferrofluid (IFF). Composed of 5% volume of small particles ( 3 -15 nm) solid, magnetic, single domain particles coated namely magnetite (Fe3O4), maghemite ( y- Fe2O3), cobalt ferrite (CoFe2O4) and other compounds having iron with a molecular layer of dispersant which suspended in 85% volume of base fluid (water, oil, ethylene glycol, etc.) as well as 10% volume of surfactants (lauric acid, oleic acid, etc.). Exhibits superparamagnetism of magnetic behavior. The understanding of ferrofluid characteristic has greatly helped the researchers in analyzing the ferrofluid flow problems in different geometries when many researchers have experimentally proven the water based magnetite nanofluid can enhance the thermal conductivity.